EVALUATION OF ANTICANCER ACTIVITY OF CUCUMIS CALLOSUS AGAINST EHRLICH’S ASCITES CARCINOMA BEARING MICE - Panda, Siva Prasad; A, Rajsekhar Reddy; Panigrahy, Uttam Prasad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Our previous research isolated Cucurbitacin B (CuB) and ebenone leucopentaacetate (ELP) from methanolic fruit extract of Cucumis callosus (MFCC). The fruits of C. callosus (Rottl.) Cogn. (Family: Cucurbitaceae) plant have been traditionally used for antioxidant, anti-inflammatory, and antidiabetic actions. The objective of this research was to evaluate in vitro and in vivo anticancer effect of MFCC on Ehrlich Ascites Carcinoma (EAC) cell lines. Methods: In vitro anticancer assay of MFCC and standard drug, 5-fluorouracil (5-FU) was evaluated using Trypan blue and 3-(4, 5-dimethylthiazol-yl)-2, 5-diphenyl tetrazolium bromide methods. In vivo anticancer activity of MFCC and 5-FU was also performed after 24h of EAC cells (2Ã—106cells/ mouse) inoculation based on toxicity study for 9 consecutive days. The activity of the extract was assessed by the study of tumor volume, tumor weight, viable and non-viable cell count, hematological parameters, and biochemical estimations. Results: The MFCC showed the direct antitumor effect on EAC cells in a dose-dependent manner with an IG50 value of 0.61 mg/ml. Furthermore, MFCC (350 mg/kg) exhibited significant (p<0.01) decrease in tumor volume, tumor weight, and viable cell count of EAC-treated mice. Hematological profile, biochemical estimation assay significantly (p<0.01) reverted to normal level in MFCC, and 5-FU treated mice. Conclusion: The anticancer activity of fruits of C callosus is may be either due to the presence of CuB or/and ELP as phytoconstituent and the activity is comparable to standard drug 5-FU.